ECONOMIC AND LEGAL ASPECT OF THE NEGATIVE IMPACT OF OIL AND GAS WELLS ON THE ENVIRONMENT - E. Yu. Kamchatova; A. V. Sedova (Вестник университета)
The negative impact on the environment is carried out from almost all oil and gas facilities. One of such objects are wells of any purpose. The causes of negative impacts on the environment from plugged and abandoned wells were identified in the course of the study. Existing methods and technologies of well liquidation and conservation have been analyzed in the article. Existing problems in the legal regulation of the issue of environmental safety of abandoned wells have been investigated. The result of comparison of the international and domestic legislation on this problem has been presented.